[Kalibo Ati-atihan, 1995 [videorecording] - Philippines. National Commission for Culture and the Arts. (Manila NCCA, 1995)
A documentation of the Ati-atihan festival, featuring a parade from the different barangays in costume, the re-enactment of the Barter of Panay and coronation of Ms. Kalibo Ati-atihan '95.
VHS.
Keywords: Ati-atihan (Festivals); Folk festivals -- Philippines -- Kalibo (Aklan); Rites and ceremonies -- Philippines -- Kalibo (Aklan)